Walking exploration of the pilgrimage route El Camino de Santiago - Crownhart, Andrea (My University, 2006)
In the fall of 2005, I walked the pilgrimage route El Camino de Santiago in northern Spain. During my time on the Camino, I interviewed fellow pilgrims to discover why people want to complete this pilgrimage, as well as evaluating my own experiences as I walked.
Color poster with text describing the research project conducted by Andrea Crownhart, advised by Dr. Margarita Hendrickson (University of Wisconsin-River Falls) that examined the pilgrimage route El Camino de Santiago.
Keywords: Semester abroad program (University of Wisconsin-River Falls); Santiago de Compostela (Spain); El Camino de Santiago; Pilgrimage route; Spain, Northern -- Description and travel; Personal narratives; Pilgrims and pilgrimages; Pilgrims and pilgrimages -- Spain -- Santiago de Compostela; Pilgrims and pilgrimages -- Spain -- Santiago de Compostela -- Personal narratives